2016
DOI: 10.1111/2047-3095.12135
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence Between NANDA International Nursing Diagnoses and Outcomes as Proposed by the Nursing Outcomes Classification

Abstract: The data evidence the relevance of this review for a reliable application of these taxonomies and demonstrated partial correspondence between concepts analyzed. A identificação precisa dos diagnósticos de enfermagem e a medida correspondente dos seus indicadores dependerá dos elementos nos sistemas de linguagem padronizados.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
(23 reference statements)
0
12
0
3
Order By: Relevance
“…In the United States, NANDA has been influential in developing a common language reflecting the complexities of nursing practices through the use of nursing diagnosis which facilitates nursing care (de Carvalho et al . ); however, these are not used in Australia. Interestingly, a Turkish study found 15–20% of nurses do not value nursing diagnosis when providing care (Akbulut & Akpinar ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the United States, NANDA has been influential in developing a common language reflecting the complexities of nursing practices through the use of nursing diagnosis which facilitates nursing care (de Carvalho et al . ); however, these are not used in Australia. Interestingly, a Turkish study found 15–20% of nurses do not value nursing diagnosis when providing care (Akbulut & Akpinar ).…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic practice within the nursing profession is controversial, with many nurses, medical officers, and allied health professionals arguing that it is outside of the nurse's scope of practice (Baid 2006;Cashin et al 2010;Sands 2009). In the United States, NANDA has been influential in developing a common language reflecting the complexities of nursing practices through the use of nursing diagnosis which facilitates nursing care (de Carvalho et al 2018); however, these are not used in Australia. Interestingly, a Turkish study found 15-20% of nurses do not value nursing diagnosis when providing care (Akbulut & Akpinar 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical validation results are very important because they provide better knowledge for the improvement of the classification while moving the theoretical knowledge closer to clinical evidence (Caldeira, Timmins, Carvalho, & Vieira, 2015). This reinforces the need to understand the factors included in the nursing diagnosis, their relationship with the clinical presentation (signs and symptoms), and possible cause (etiology) in order to gain practice with efficient and measurable interventions (Carvalho et al, 2016). More validation studies using specialist nurses and patients in clinical settings are necessary to refine the defining characteristics, to discuss the taxonomy structure, and to contribute to the completeness and coherence of the taxonomy (Caldeira, Carvalho, & Vieira, 2013).…”
Section: Introductionmentioning
confidence: 98%